Technical Efficiency Analysis of Stunting Intervention Programs in Central Java Province: A Two-Stage Data Envelopment Analysis (DEA) Approach - Anggie Neva Deliza; Nenik Woyanti (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2024)
Stunting remains a major challenge to human development in Indonesia, as it directly affects the quality of human resources and long-term economic productivity. Central Java Province is among the national priority areas for stunting reduction; however, the efficiency of its intervention programs remains suboptimal. This study aims to analyze the technical efficiency of stunting intervention programs in Central Java Province during the 2019–2023 period by applying a Two-Stage Data Envelopment Analysis (DEA) approach. The study employs secondary data obtained from the Central Statistics Agency (BPS), the Central Java Provincial Health Office, and the Directorate General of Fiscal Balance of the Ministry of Finance of the Republic of Indonesia. Input variables include the percentage of infants receiving exclusive breastfeeding, the percentage of infants with complete basic immunization, the percentage of deliveries in health facilities, and the percentage of households with access to safe drinking water and proper sanitation. The output variable is represented by the percentage of children under five with normal nutritional status (height-for-age). The findings reveal that only 5.71 percent of districts or municipalities in Central Java achieved perfect technical efficiency, namely Banjarnegara and Grobogan Regencies. This indicates that most regions have not yet optimized their resources and health service capacities to achieve effective stunting interventions. The study highlights the need for strengthened intersectoral coordination, improvement of basic health service facilities, and better allocation of nutrition-related budgets to enhance systemic efficiency in reducing stunting prevalence at the regional level.